THE ROLE OF ZAKAT IN THE ECONOMIC EMPOWERMENT OF THE COMMUNITY IN SURABAYA CITY - Fadhil Muhammad Akbar; Siti Kalimah (Jurnal Ilmiah Al-Tsarwah, 2025)
Zakat as an Islamic social finance instrument plays a strategic role in transforming socio-economic conditions and reducing poverty in urban areas. This research analyzes the role of zakat in empowering Surabaya City community through productive zakat programs. Methods: This qualitative research uses library research approach. Data were collected from peer-reviewed journals, BAZNAS and LAZNAS reports, and academic books on Islamic economics. Sources were selected using purposive sampling focusing on Surabaya City context. Productive zakat significantly empowers Surabaya's economy through programs like "Surabaya Berdaya". Studies show productive zakat increases mustahik welfare by 38%, reduces poverty by 51.9%, and improves independence index from scale 2 to 4. Mosques play a strategic role as economic empowerment centers integrating ZIS funds. Challenges include gaps between zakat potential and realization, limited institutional capacity, and business sustainability issues. Zakat has great potential for inclusive economic development in Surabaya through transformation from consumptive to productive approach. Comprehensive empowerment mechanisms effectively transform mustahik into independent economic actors. Optimization requires strengthening regulations, institutional capacity, adaptive models, and monitoring systems. Recommendations include developing innovative programs, strengthening supportive policies, and conducting detailed quantitative studies on mustahik welfare impacts.